Analysis of end-spurt behaviour in elite 800-m and 1500-m freestyle swimming - Neuloh, J. E.; Skorski, S.; Mauger, L.; Hecksteden, A.; Meyer, T. (European Journal of Sport Science, 2020)
To analyse the influence of distance, time point of competition, round and finishing position on end-spurt behaviour in swimming. Race results in 800-m and 1500-m freestyle swimming from the last 8 World Championships and 5 Olympic Games (1998-2016) including 1433 races and 528 swimmers were obtained. The endspurt for each race was determined by means of an End-Spurt Indicator (ESI). The ESI was calculated by dividing the difference between the swim velocity of the last lap (SVLL) and the mean swim velocity of the middle part of the race (SVMP) by the respective individual standard deviation of SVMP. Subsequently, ESI was used as a dependent variable and influences were analysed using a linear mixed model with fixed effects for distance, time point of competition, round and finishing position. An end-spurt was evident in most swims for both race distances. The mean change in swim velocity between the middle part of the race and the last lap was 0.06 ± 0.02 m/s (1.2 ± 0.2 s) in the 800-m and 0.07 ± 0.02 m/s (1.5 ± 0.2 s) in the 1500-m. The finishing position within a race significantly affected the ESI (P < .001, t = 7.28). Specifically, when analysing finals only, ESI was significantly greater in medallists (5.76; quantile: 3.61 and 8.06) compared to non-medallists (4.06; quantile: 1.83 and 6.82; P = .001). The between-subject standard deviation was 1.66 (Cl: 1.42-1.97) with a relative variance component of 23%, while 77% of ESI variance remained unexplained. This is the first study using a newly developed indicator of endspurt behaviour demonstrating that particularly medallists have a more pronounced end-spurt compared to non-medallists.